KEBERADAAN KEBUTUHAN EXISTENCE, RELATEDNESS, GROWTH, DALAM VIDEO GAME HARVEST MOON BACK TO NATURE - Arief Budiman (LPPM Institut Bisnis dan Teknologi Indonesia, 2019)
Playing video games is basically an activity where it must have an stimulus energy which is commonly referred to as motivation. Without motivation, player will not be interested in playing a video game with a long duration. The Harvest Moon Back to Nature video game as a video game that was quite successful, which made the video game a legendary video game for the audience's audience as early as 1997. It creates interest which in turn encourages researchers to know more about how motivation for human needs is presented by the Harvest Moon Back to Nature video game. This research fundamentally use interpretative analytical descriptive method with narrative approach. Using a view from ERG theory Alderfer, which according to him motivation is related to basic human needs which consist of existence needs, relatedness needs, and growth needs.. From the results of the research conducted using these instruments, it can be concluded that the power of motivation has been presented in the Harvest Moon Back to Nature video game from the fulfillment of existence needs, relatedness needs, and growth needs, both in the context events of farming, raising, and in carrying out other events.